ANTROPOMETRY AND PHYSICAL FITNESS FACTORS DETERMINANT DRIBBLING AND PASSING FUTSAL ABILITY OF STUDENT EXTRACURRICULAR AGED 12-15 YEARS - Ramadaniawan, Nizamuddin Nur; Sugiyanto, Sugiyanto; Siswandari, Siswandari (International Journal of Education, 2018)
The objective of this study is to investigate anthropometric factors and physical fitness as determinants of futsal dribbling and passing skills of students aged 12-15 years. The population of this study was all extracurricular futsal players in Surakarta with a sample of 50 students obtained by simple random sampling technique. Data collection techniques used were tests and measurements. The data were analyzed with testing factor confirmatory analysis with the help of SPPS and Amos 21 program. The results of hypothesis testing proved that the overall anthropometric factors and physical fitness had a relationship to the skills of futsal dribbling and passing. The factors include: (1) Foot length with a regression coefficient value of 0.689, (2) Coordination with a regression coefficient value of 0.453, (3) Speed with a regression coefficient value of 0.237, (4) Endurance with a regression coefficient value of 0.229, (5) Flexibility with a regression coefficient value of 0.220, (6) Balance with a regression coefficient value of 0.237, and (7) Limb length with a regression coefficient value of -726. It can be concluded that the dominant factor to determine futsal dribbling and passing skills for 12-15 years old students is foot length.